Glycoursodeoxycholic acid and interleukin-10 modulate the reactivity of rat cortical astrocytes to unconjugated bilirubin - Fernandes, Adelaide (2015)
The pathogenesis of bilirubin encephalopathy seems to result from accumulation of unconjugated bilirubin (UCB) within the brain. We have recently demonstrated that UCB causes astroglial release of proinflammatory cytokines and glutamate, as well as cell d